Three new species of crustose Teloschistaceae in Siberia and the Far East. (May 2021) - Frolov, Ivan V.; Vondrák, Jan; Konoreva, Liudmila A.; Chesnokov, Sergey V.; Himelbrant, Dmitry E.; Arup, Ulf; Stepanchikova, Irina S.; Prokopiev, Ilya A.; Yakovchenko, Lidia S.; Davydov, Evgeny A.
Abstract: Three species of the family Teloschistaceae (lichenized Ascomycota) are described as new to science from Southern and Eastern Siberia and the Far East. Corticolous Caloplaca saviczii belongs to the genus Caloplaca s. str.; it has C. cerina -like apothecia and green to grey-green, crateriform soralia with a white rim. Lendemeriella aureopruinosa is a saxicolous taxon with a thin grey thallus and small apothecia 0.3–0.6 mm in diameter, with a dark orange disc usually bearing epipsamma and often with a grey true exciple containing the pigment Cinereorufa-green. Orientophila infirma is a corticolous species with an endophloeodal thallus and small orange apothecia, 0.2–0.3 mm in diameter, usually with an inconspicuous thalline exciple. All new taxa presumably have a boreal north-eastern distribution in Asia.